Deciphering the Role of Holin in Mycobacteriophage D29 Physiology - Bavda, Varun Rakeshbhai; Jain, Vikas (Frontiers in Microbiology, 2020)
In the era of antibiotic resistance, phage therapy is gaining attention for the treatment of pathogenic organisms such as Mycobacterium tuberculosis. The selection of phages for therapeutic purposes depends upon several factors such as the host range that a phage can infect, which can be narrow or broad, time required for the host cell lysis, and the burst size. Mycobacteriophage D29 is a virulent phage that has the ability to infect and kill several slow- and fast-growing mycobacterial species including the pathogenic M. tuberculosis. It, therefore, has the potential to be used in phage therapy against M. tuberculosis. D29 lytic cassette encodes three proteins viz. peptidoglycan hydrolase (LysA), mycolylarabinogalactan esterase (LysB), and holin, which together ensure host cell lysis in a timely manner. In this work, we have scrutinized the importance of holin in mycobacteriophage D29 physiology. Bacteriophage Recombineering of Electroporated DNA (BRED) approach was used to generate D29 holin knockout (D29Δgp11), which was further confirmed by the Deletion amplification detection assay (DADA)-PCR. Our results show that D29Δgp11 is viable and retains plaque-forming ability, although with reduced plaque size. Additionally, the host cell lysis governed by the mutant phage is significantly delayed as compared to the wild-type D29. In the absence of holin, D29 shows increased latent period and reduced burst size. Thus, our experiments show that while holin is dispensable for phage viability, it is essential for the optimal phage-mediated host cell lysis and phage propagation, which further points to the significance of the ‘clock’ function of holin. Taken together, we show the importance of holin in governing timely and efficient host cell lysis for efficient progeny phage release, which further dictates its critical role in phage biology.